Restriction of Toeplitz Operators on Their Reducing Subspaces. (7th September 2017) - Xu, Anjian; Zou, Yang
Abstract : We study the restrictions of analytic Toeplitz operator on its minimal reducing subspaces for the unit disc and construct their models on slit domains. Furthermore, it is shown that T z n is similar to the sum of n copies of the Bergman shift.